(untitled) (Scientific journal of the Fergana State University, 2024)
Phytoremediation method is an effective and easy way to remove heavy metals through plants, for this it is only necessary to know how to choose the type of plant suitable for the area. Some phytoremediation plants can absorb heavy metals and transfer them to a harmless state in their cells, such plants can be harvested or planted in the soil as siderate crops. This will benefit both the farmers and the fallow land. The presence of green plants around polluting sources ensures constant renewal of the area with oxygen. Using this method does not require a lot of money, just enough time and money for planting and watering processes. Heavy hands and constant control are not necessary for such crops, if the plant is chosen correctly. There are a number of processes involved in the accumulation of heavy metals in plants, including heavy metal mobilization, root uptake, xylem loading, root-to-shoot transport, cell division, and translocation. Heavy metals are mainly present in the soil in an insoluble form and are not biologically available for plants.